Animation Movie Video as Media in Teaching Speaking Skill - Dasriani Zain; Syahrir L; Andi Asrifan; Sam Hermansyah (Edumaspul: Jurnal Pendidikan, 2024)
This study investigates the effectiveness of using animation movies as a medium to improve learners' speaking skills, focusing particularly on vocabulary and pronunciation. The findings demonstrate a significant improvement in learners' speaking performance, as evidenced by the comparison of pre-test and post-test results. The mean score increased from 51.77 in the pre-test to 83.87 in the post-test, highlighting the substantial impact of the animation movie approach. Statistical analysis using a paired-sample t-test further supports these results, with a p-value of 0.000, indicating significance at the 0.05 level (p < 0.05). This confirms the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1), validating the effectiveness of the intervention. The use of animation movies proved to be an appropriate and beneficial strategy in the teaching and learning process, as it enhances learners' ability to understand pronunciation and memorize vocabulary. The findings suggest that animation movies can serve as an effective medium for teaching speaking skills, particularly in improving pronunciation and vocabulary acquisition. Consequently, the study concludes that incorporating animation movies into the learning process significantly boosts learners' speaking proficiency.